Recombinant C1q variants modulate macrophage responses but do not activate the classical complement pathway. (January 2020) - Espericueta, Victoria; Manughian-Peter, Ayla O.; Bally, Isabelle; Thielens, Nicole M.; Fraser, Deborah A.
Graphical abstract: Recombinant C1q Variants rC1qB and rC1qC contain mutations in the C1q B-chain ( Lys61-Ala) or C-chain ( Lys58-Ala) respectively, that render them unable to interact with and and activate the classical complement pathway. They still retain the ability to modulate phagocyte responses. A region similar to the sequence identified in MBL as necessary for enhancement of phagocytosis is located below the hinge region in the C1q A-chain ( ). Highlights: Recombinant C1q variants were expressed that do not activate the classical complement pathway. Recombinant C1q variants modulate phagocytosis similar to wild-type C1q. Recombinant C1q variants modulate macrophage cytokines and chemokines similar to wild-type C1q. Abstract: Complement protein C1q plays a dual role in a number of inflammatory diseases such as atherosclerosis. While in later stages classical complement pathway activation by C1q exacerbates disease progression, C1q also plays a beneficial role in early disease. Independent of its role in complement activation, we and others have identified a number of potentially beneficial interactions of C1q with phagocytes in vitro, including triggering phagocytosis of cellular and molecular debris and polarizing macrophages toward an anti-inflammatory phenotype. These interactions may also be important in preventing autoimmunity. Here, we characterize variants of recombinant human C1q (rC1q) which no longer initiate complement activation, through mutation of the C1r2 C1s2 interaction site. For insight into the structural location of the site of C1q that is important for interaction with phagocytes, we investigated the effect of these mutations on phagocytosis and macrophage inflammatory polarization, as compared to wild-type C1q. Phagocytosis of antibody coated sheep erythrocytes and oxidized LDL was measured in human monocytes and monocyte-derived macrophages (HMDM) respectively that had interacted with rC1q wild-type or variants. Secreted levels of cytokines were also measured in C1q stimulated HMDM. All variants of C1q increased phagocytosis in HMDM compared to controls, similar to native or wild-type rC1q. In addition, levels of certain pro-inflammatory cytokines and chemokines secreted by HMDM were modulated in cells that interacted with C1q variants, similar to wild-type rC1q and native C1q. This includes downregulation of IL-1α, IL-1β, TNFα, MIP-1α, and IL-12p40 by native and rC1q in both resting and M1-polarized HMDM. This suggests that the site responsible for C1q interaction with phagocytes is independent of the C1r2 C1s2 interaction site. Further studies with these classical pathway-null variants of C1q should provide greater understanding of the complement-independent role of C1q, and allow for potential therapeutic exploitation.